THE ROLE AND CONTRIBUTION OF INDONESIAN WORKERS IN THE GLOBAL MARKET AND ECONOMIC INTERNATIONAL (MALAYSIA) - Mei Linda, Sinta (Proceeding of International Conference on Multidisciplinary Research, 2024)
Indonesia's workforce, especially those working abroad, plays an important role in the global market, contributes significantly to the international economy, and supports economic growth and social development, especially in Malaysia. In this article, we will discuss the impact of the presence of Indonesia's migrant workers on the Malaysian economy and how their contribution affects the bilateral economic relationship between Indonesia and Malaysia. This study also aims to analyze the contribution of Indonesia's workforce to the dynamics of the global market and the international economy in the context of Malaysia. The method used is qualitative analysis by collecting data from various sources of literature and field surveys. The results show that Indonesia's migrant workers not only meet the needs of Malaysia's labor-intensive sectors, such as construction and services but also have a positive impact through remittances that contribute to the local economy in Indonesia. However, challenges in protecting workers' rights remain an issue that needs to be addressed. The study concludes that collaboration between the governments of Indonesia and Malaysia is essential to ensure the welfare and protection of the workforce, as well as to maximize the positive contribution to the economies of both countries.